Pengaruh Orientasi Etika terhadap Komitmen Akuntan Publik pada Profesi dan Organisasi - Setianingsih, Sunarti (Jurnal Widya Manajemen & Akuntansi, 2007)
Ethics is accepted behavior values and used by individual or certain group. The ethical attitude of an auditor is determined not only by the rule of hi professional ethical code, but also by cultural, profession's, organizational environment, and personal experience. The objective of the research was to determine the effect ethical orientation on commitment public accountant to organization and profession. Data were obtained through the use of questioners from fifty nine experienced public accountants from CPA firm at Bandung area. Questionnaires were designed to provide data on three variables: ethical orientation, organization commitment and professional commitment. The data were analyzed using simple regression technique. The result of analysis indicated that ethical orientation has direct effect organization commitment and professional commitment. The relationship between organization commitment and professional commitment is also stronger. The higher level of professional commitment of public accountant there will also be a higher degree of organization commitment. The result has implication to public accountant seeking to explain why ethical is needed. This research also proposes the direction for future research in behavioral accounting area.